Introduction of the first antimalarial vaccine: A step towards Malaria eradication? - Asmar, Abyaz; Farooq, Hareem; Aemaz Ur Rehman, Muhammad (Journal of the Pakistan Medical Association, 2022)
Madam, malaria is a potentially fatal parasitic infection caused by Plasmodium species. It presents with a various nonspecific clinical symptoms ranging from mild febrile illness to severe organ damage. (1) Life-threatening complications like cerebral malaria, renal failure, circulatory shock, and acute respiratory distress may also occur, most commonly due to Plasmodium Falciparum species. (1) Despite extensive research and new treatment guidelines, malaria is still reported to be endemic in around 100 countries, with almost 50% of the world’s population at risk. (1,2) Moreover, it is responsible for about 409 thousand deaths per year, with the majority being caused by the Falciparum strain. (2) The treatment of malaria is limited by drug resistance, and the lack of universally effective drugs makes the situation all the more challenging. (1). In early October, the World Health Organization (WHO) made the historic recommendation of RTS,S/AS01 (RTS,S) malaria vaccine against P. falciparum, for children in moderate to high transmission areas. (3) Many malaria cases over a 3-4 year period were prevented by the vaccine as per the results of phase 3 trials conducted in Africa. (4) With the help of national ministries, a pilot program is currently underway (2019-2023) in Ghana, Kenya, and Malawi. (5) The encouraging preliminary results of this program have led to the guidelines regarding the widespread use of the vaccine. (3) Outside tropical Africa, 80% of malaria cases are reportedly found in Asia. (1) With 3.5 million suspected and confirmed annual malaria cases, Pakistan is listed as a moderate malaria-endemic country where 60% of the population is at risk of developing the disease. (6) Hence, in addition to the proper implementation of pre-existing prevention and treatment strategies against malaria, developing a national vaccine program is the need of the hour. It is a chance for the health sector of Pakistan to collaborate with WHO towards the implementation of this program. The focus should primarily be on high prevalence regions, such as tribal areas and areas affected most by seasonal variation. The introduction of this vaccine is a groundbreaking step towards the global eradication of malaria and is even more important for developing countries like Pakistan where malaria causes an increased burden on healthcare resources and the economy. Given the extremely encouraging results from trials, it is projected to significantly decrease morbidity and mortality, especially in children.